TUBERCULOSIS CONTROL PROGRAM IN MEXICO - ALARCON, DONATO G (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1977)
The antituberculo- sis campaign in Mexico is provided almost entirely by govtl agencies Direct means of control are the major concern of 33 dispensaries; these conduct an extensive ambulatory treatment service and direct selected cases to appropriate in
AM REV TUBERCUL
Keywords: TUBERCULOSIS, PROGRAM, MEXICO; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA